How do the Local Physical, Biochemical, and Mechanical Properties of an Injectable Synthetic Anisotropic Hydrogel Affect Oriented Nerve Growth?. (5th August 2022) - Babu, Susan; Chen, I; Vedaraman, Sitara; Gerardo‐Nava, José; Licht, Christopher; Kittel, Yonca; Haraszti, Tamás; Di Russo, Jacopo; De Laporte, Laura
Abstract: As an injectable tissue regenerative platform, Anisogel aims to recapitulate the complex and anisotropic architecture of native extracellular matrix by the use of magneto‐responsive microgels, which are oriented under a low magnetic field of ≈100 mT, while a surrounding hydrogel matrix cross‐links around them. This system promotes the oriented growth of neurons when cultured in vitro. In this study, how the local microgel properties affect neurite outgrowth and orientation is aimed to understand using dorsal root ganglia from chicken embryos. When the surrounding matrix is a synthetic poly(ethylene glycol) hydrogel, the microgel concentration and length required to achieve oriented nerve growth is higher compared to fibrin‐based Anisogels. Microgels should be stiffer than the matrix for cells to sense the mechanical anisotropy but a wide range of microgel stiffness leads to similar cell alignment and growth. On the other hand, modification of the microgels with common extracellular matrix molecules enhances nerve growth but deteriorates nerve alignment compared to bioinert microgels in a cell adhesive surrounding gel. Finally, covalently coupling these microgels to the surrounding matrix reduces both cellular orientation and outgrowth suggesting a reduction in the ability of cells to sense the anisotropy. Abstract : Understanding the role of local biophysical, mechanical, and chemical cues in 3D matrices to direct cell growth is important to make suitable tissue regenerative scaffolds that mimic native extracellular matrices. With the use of an anisotropic hydrogel platform, called Anisogel, orthogonal signaling cues from magnetically oriented rod‐shaped microgels and a surrounding hydrogel matrix are presented to primary nerve cells.